2016
DOI: 10.1186/s12884-016-1144-0
|View full text |Cite
|
Sign up to set email alerts
|

Clinicians’ views of factors of importance for improving the rate of VBAC (vaginal birth after caesarean section): a study from countries with low VBAC rates

Abstract: BackgroundCaesarean section (CS) rates are increasing worldwide and the most common reason is repeat CS following previous CS. For most women a vaginal birth after a previous CS (VBAC) is a safe option. However, the rate of VBAC differs in an international perspective. Obtaining deeper knowledge of clinicians’ views on VBAC can help in understanding the factors of importance for increasing VBAC rates. Focus group interviews with clinicians and women in three countries with high VBAC rates (Finland, Sweden and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
46
1

Year Published

2017
2017
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(47 citation statements)
references
References 40 publications
0
46
1
Order By: Relevance
“…A survey on 44 doctors from countries with VBAC rate > 45% outlined that their confidence with VBAC, working in a united obstetric team positively interacting with each other and with women on defined targets (discussed with the parturients) and following structured strategies contributed to enhanced the VBAC rate 83 . This was confirmed by another survey on 71 doctors from countries with VBAC rates < 36%, stressing the importance of a shared informed decision between women and obstetricians, supported by inter-personal trustfulness, adequate clinical skill/confidence of the obstetric team and clinical decisions sustained by scientific evidence 84 . In another qualitative study based upon focus groups on 22 and 51 women from countries with high 85 and low 86 VBAC rates, women expressed desire for correct information on VBAC from doctors and to share with them the decision-making on DM.…”
Section: Prospectsmentioning
confidence: 73%
See 1 more Smart Citation
“…A survey on 44 doctors from countries with VBAC rate > 45% outlined that their confidence with VBAC, working in a united obstetric team positively interacting with each other and with women on defined targets (discussed with the parturients) and following structured strategies contributed to enhanced the VBAC rate 83 . This was confirmed by another survey on 71 doctors from countries with VBAC rates < 36%, stressing the importance of a shared informed decision between women and obstetricians, supported by inter-personal trustfulness, adequate clinical skill/confidence of the obstetric team and clinical decisions sustained by scientific evidence 84 . In another qualitative study based upon focus groups on 22 and 51 women from countries with high 85 and low 86 VBAC rates, women expressed desire for correct information on VBAC from doctors and to share with them the decision-making on DM.…”
Section: Prospectsmentioning
confidence: 73%
“…A number of interventions may be adopted to facilitate this process of change: education of staff/patients by opinion leaders; introduction of a second opinion for all CS; prenatal counselling for women and partners [82][83][84][85]112 . Although, clinical audits, financial penalties and rewards to maternity centres could also be considered.…”
Section: Discussionmentioning
confidence: 99%
“…Sites randomised to the intervention group received a complex, innovative programme of evidence-based antenatal strategies, developed following three systematic reviews [17,20,21], and four qualitative studies with clinicians and women in both high and low VBAC countries [18,19,24,25]. Technology-assisted learning resources were also developed using motivational systems and instructional design theory [26].…”
Section: Interventionsmentioning
confidence: 99%
“…Findings from a recent systematic review of clinicianfocussed interventions showed that the only strategy that significantly increased VBAC rates was an educational intervention provided by an opinion leader [17]. A study of 44 clinicians practising in three countries with high VBAC rates (> 45%) [18], and a similar study based on 71 clinicians from countries with low VBAC rates [19] showed comparable findings related to trust in the clinician-woman relationship, a positive attitude of all centrally involved, early follow-up and fear reduction. However, differences shown related to the decisionmaking process, parameters for VBAC, organisational support and resources, and clinical expertise, which indicate different attitudes and views among clinicians in countries with high and low VBAC rates.…”
Section: Introductionmentioning
confidence: 99%
“…In other hand, Susan found most women hadn't enough counseled about delivery and it was affected by many factors [29]. All things considered, give them more supports and encouragements, strengthen the confidence of vaginal delivery, increase care and decrease the fear [30].…”
Section: The Favorable Factors To Vaginal Delivery After Cesarean Secmentioning
confidence: 99%